AVAILABILITY AND STORAGE CONDITIONS OF ESSENTIAL MEDICINES AT PRIMARY HEALTHCARE FACILITIES IN PUNJAB, PAKISTAN - Hussain, Rizwana; Mahmoud Radwan; Sadia Habib (Journal of Ayub Medical College Abbottabad, 2021)
Background: Availability of essential medicines is one of the most important universal human right. For one third of the world, unavailability of essential medicines remains a major problem. The objective of this study is to authenticate the availability of essential medicines along with the storage conditions at primary healthcare level, district central warehouses and private pharmacies in the rural areas. Method: A community based cross-sectional survey was conducted in five districts of Punjab, Pakistan. Data was collected retrospectively and prospectively, by World Health Organization (WHO) tool, Operational Package for Assessing, Monitoring and Evaluating Country Pharmaceutical Situations. Results: On an average availability of essential medicines in primary healthcare, private pharmacies, and warehouses were 90.32±1.78 (SD), 82.83±2.75 (SD) and 96±0.83 (SD), respectively. Stock out duration of essential medicines in primary healthcare and district central warehouses were 11.56±4.08 (SD) and 10.24±5.95 (SD) respectively. Expired medicines were not found. Storage conditions of medicines in store room in PHC, private pharmacies and district central warehouses were 75.76±1.53(SD), 73.33±2.16 (SD), and 82.0±2.48 (SD) respectively. Storage conditions of dispensing room in PHC and private pharmacies were 66.06±2.52 (SD) and 39.65±4.25 (SD) respectively. Conclusion: Availability of essential medicines was below WHO standards. Medicines were found to be stocked out. No expired medicine was found on shelves. Storage conditions of medicines were poor.